2009
DOI: 10.1002/ejlt.200900020
|View full text |Cite
|
Sign up to set email alerts
|

Protecting oil during frying: A comparative study

Abstract: The effect of carbon dioxide blanketing (CDB) and vacuum frying (VF) on the frying performance of regular canola oil was evaluated. For 7 h daily and for 7 days French fries were fried in regular canola oil at 185 6 5 7C without and with CDB and in a vacuum fryer. The extent of changes in the oil was assessed by analysis of total polar compounds (TPC), anisidine value (AV), color component formation and changes in composition of fatty acids and tocopherols. Frying under CDB reduced the amount of TPC by 54%, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
50
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 18 publications
2
50
0
Order By: Relevance
“…Exposure of oil to excessive heating in the pres-oil with air is minimal when the oil surface area to volume ratio is relatively small 8 . Flushing the frying oil with inert gases like carbon dioxide and/or nitrogen helps to reduce the concentration of dissolved oxygen 9,10 . Frying at elevated pressure 11 and under vacuum 9 protects frying oil against deterioration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure of oil to excessive heating in the pres-oil with air is minimal when the oil surface area to volume ratio is relatively small 8 . Flushing the frying oil with inert gases like carbon dioxide and/or nitrogen helps to reduce the concentration of dissolved oxygen 9,10 . Frying at elevated pressure 11 and under vacuum 9 protects frying oil against deterioration.…”
Section: Introductionmentioning
confidence: 99%
“…Flushing the frying oil with inert gases like carbon dioxide and/or nitrogen helps to reduce the concentration of dissolved oxygen 9,10 . Frying at elevated pressure 11 and under vacuum 9 protects frying oil against deterioration. Ahmad Tarmizi et al 12 observed that the shelf life of frying oil can be improved when applying vacuum during the post-frying stage.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, saturated and hydrogenated oils are frequently used for frying applications, despite their health negative effects. [8][9][10] Tocopherols are natural occurring potent antioxidants that help to prevent the oxidation of unsaturated fatty acids (USFAs). Tocopherols including α-, β-, γ-and δ-homologous are considered to be highly anti--oxidants.…”
Section: Introductionmentioning
confidence: 99%
“…Displacing the air at the surface of the oil with carbon dioxide obstructs the supply of oxygen to the oil. Aladedunye et al 9 heated 4 L of canola oil at 185 5 under a flow of 150 L/h carbon dioxide and fried 8 batches of French fries per day for 7 continuous days and found that oxidation of the oil was remarkably reduced. However, the rather high cost of modifying common fryers and of carbon dioxide limits this approach 10 .…”
Section: Introductionmentioning
confidence: 99%